Seven ways to get a grip on facilitating bedside team rounding - Ibrahim, Syed Mohammad; Shuster, Shirley; Aina, Deborah; Wijeratne, Don Thiwanka (Canadian Medical Education Journal, 2020)
Although classically considered a cornerstone of inpatient care, rounding at patients’ bedsides is increasingly being replaced by rounding in workrooms. Workroom rounds may provide a sense of efficiency and comfort, however bedside rounds have multiple benefits for patients, trainees and staff physicians. Alongside its benefits, there are human and institutional challenges when incorporating bedside rounding. This article aims to draw on our own experience of implementing bedside rounding at Kingston Health Sciences Centre, to guide staff physicians and institutions on how to implement bedside rounding effectively while overcoming its challenges. The following seven tips provide a framework to avoid pitfalls when implementing bedside team rounding on inpatient services.